Kisvárosaink – A településhálózat köztes helyzetében (Előtanulmány és hipotézis) - Bánlaky, Pál (Tér és Társadalom, 1987)
The question the paper seeks to answer – ín the form of a theoretical hypothesis is what are the peculiar, distinguishing features of small towns in the present network of Hungarian settlements. The author emphasizes that his approach is sociological: he is concerned with the social factors, the social functions system of a small town. The introduction contains the outlines of a dimension-system which is supposed to illustrate the peculiar character of small towns (the features that distinguish them from villages, and medium-sized or large towns). The dimensions considered here are the following: I. Social – macrostructural dimensions: 1. Position within the hierarchy of settlements 2. Historic development, the way in which the present settlement was shaped II. Dimensions of economic and social division of labour: 1. Differentiation in the economic structure of the settlement 2. The structure of jobs and other social activities: homogenity or differentiation, coordination or interrelationship. III. Dimensions of structural character: 1. The inner social structure of the settlements 2. The political structure of the local societies 3. Scope of individual actions; represented along the axes „large-narrow" and „conformity–deviation". The author analyzes these dimensions one be one and describes the differences, partly hypothetic, or proved by previous studies observed among the settlement types. In the final part the author returns to the dimensions and states that the distinguishing features basically fall into two groups; one contains those that serve as a basis for establishing the categories, and the other containing mostly the qualifying features. (The category features are: position within the hierarchy of settlements, the character of jobs and other activities, the existence of a relative social unity. The qualifying features are: the nature of historical consciousness, the extent of economic differentiation, the proportion of urban or rural ways of life, the structure of local power, the scope of social activity and its nature.) It is the features contained in the first group that allow us to state which type a settlement belongs to (village, small town, etc.... ) The qualifying features may serve as starting points for some given, empirical research into a local society.